Experimental Method to Discriminate RAFT Models between Intermediate Termination and Slow Fragmentation via Comparison of Rates of Miniemulsion and Bulk Polymerization. Issue 3 (12th February 2014) - Suzuki, Kiyoshi; Kanematsu, Yuta; Miura, Takashi; Minami, Masayuki; Satoh, Shuzaemon; Tobita, Hidetaka; Tobita, Hidetaka; Zhu, Shiping
<x xml:space="preserve">Abstract</x> A simple model discrimination method for RAFT polymerization mechanism, proposed on a theoretical basis, is applied to the polystyryl dithiobenzoate‐mediated styrene polymerization. It is confirmed that the intermediate termination (IT) is the major reason for the rate retardation. The method utilizes the theoretical finding that the IT model shows a significantly larger polymerization rate in miniemulsion compared with the corresponding bulk polymerization, while the slow fragmentation model does not change the polymerization rate. The miniemulsion polymerization rate increases as the droplet size is made smaller, which agrees reasonably well with the theoretical prediction. The present model discrimination method is easy to apply, and would provide great insight into both basic and applied research in RAFT polymerization.<inline-graphic xlink:href="ark:/27927/pgg4sxsk1g1" content-type="mats201300150-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />